TINJAUAN YURIDIS PADA SURAT EDARAN MAHKAMAH AGUNG NOMOR 3 TAHUN 2000 TENTANG PUTUSAN SERTA MERTA (UIT VOERBAAR BIJ VOORAAD) DAN PROVISIONIL TERHADAP PUTUSAN PAILIT YANG BERSIFAT SERTA MERTA - Nandhi Larasati, Anak Agung; Dyah Satyawati, Ni Gusti Ayu (Kertha Semaya : Journal Ilmu Hukum, 2013)
Bankruptcy decision is uit bij voerbaar vooraad, which means a decision that isable to be executed even it is not legally enforceable and the debtor who declaresbankrupt is taking a legal action. It raises an issue what if the decision on appellatedecides that the debtor is not yet considered bankrupt and all the valuable assets hasbeen executed. This paper uses the normative analytical methodny reviewing literaturesand regulations regarding the issue. With the Supreme Court Circular No. 3 of 2000,the judge in deciding a case shall order the creditor to give warranty which has thesame value to other objects if later, the judge decides to revoke the desicions of thecourt of first.
Keywords: Bankruptcy, Desicion, Implication